The Strengthening and Internalisation of Ta'limul Muta'allim Values in Ma'had Darul Qur'an Wal Hadith Al-Majidiyyah As-Syafi'iyyah NW Pancor Lombok, Indonesia - Fathur Rahman Muhtar (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2021)
This study aims to reveal the tradition of character education principles in Ma'had Darul Qur'an Hadith (MDQH) Al-Majidiyah As-Shafi'iyah Nahdlatul Wathan Pancor, Mataram, based on the principles in Ta'limul Mutaallim. This research is qualitative research that uses a phenomenological approach. Sampling was done by purposive and snowball sampling. To determine the sample purposively, the researcher interviewed several informants from the teaching staff. On the other hand, in snowball sampling, the researcher explores in-depth interviews based on the recommendations of previous informants to collect data from several other informants. Furthermore, data was also collected through observation by directly observing student learning and documenting attitudes recorded in school records such as student conditions and Ma'had's profile. The collected data is then analyzed into an immersive study using the Miles and Huberman model, where the data is analyzed interactively and persistently until it is complete and the data is saturated. The results of this study indicate that studying the Book of Ta'limul al-Muta'alim will make students (santri) of Ma'had Darul Qur'an Hadith have morals such as sincerity (ikhlās), contention (istiqāmah), and patience (ṣabr).